Analysis and evaluation of law number 12 of 2012 concerning higher education based on sports needs for students - Sandey Tantra Paramitha; Muhamad Fahmi Hasan; Leni Anggraeni; Marisa Noviyanti Fajrah Ilsya; Muhamad Gilang Ramadhan; Apriya Maharani Rustandi; Hikmat Kodrat (Universitas Negeri Yogyakarta, 2021)
The sense of responsibility to educate students as